The impact of trauma relevant concentrations of prostaglandin E2 on the anti-microbial activity of the innate immune system - Nicholson, Thomas; Belli, Antonio; Lord, Janet M.; Hazeldine, Jon (Frontiers in Immunology, 2024)
Background: The mechanisms underlying the state of systemic immune suppression that develops following major trauma are poorly understood. A post-injury increase in circulating levels of prostaglandin E2 (PGE2) has been proposed as a contributory factor, yet few studies have addressed how trauma influences PGE2 biology. Methods: Blood samples from 95 traumatically-injured patients (injury severity score ≥8) were collected across the pre-hospital (≤2 hours), acute (4-12 hours) and subacute (48-72 hours) post-injury settings. Alongside ex vivo assessments of lipopolysaccharide (LPS)-induced cytokine production by monocytes, neutrophil reactive oxygen species production and phagocytosis, serum concentrations of PGE2 and its scavenger albumin were measured, and the expression of enzymes and receptors involved in PGE2 synthesis and signalling analysed. Leukocytes from trauma patients were treated with cyclooxygenase (COX) inhibitors (indomethacin or NS-398), or the protein kinase A inhibitor H89, to determine whether injury-induced immune suppression could be reversed by targeting the PGE2 pathway. The effect that trauma relevant concentrations of PGE2 had on the anti-microbial functions of neutrophils, monocytes and monocyte-derived macrophages (MDMs) from healthy controls (HC) was examined, as was the effect of PGE2 on efferocytosis. To identify factors that may trigger PGE2 production post-trauma, leukocytes from HC were treated with mitochondrial-derived damage associated molecular patterns (mtDAMPs) and COX-2 expression and PGE2 generation measured. Results: PGE2 concentrations peaked in blood samples acquired ≤2 hours post-injury and coincided with significantly reduced levels of albumin and impaired LPS-induced cytokine production by monocytes. Significantly higher COX-2 and phospholipase A2 expression was detected in neutrophils and/or peripheral blood mononuclear cells isolated from trauma patients. Treatment of patient leukocytes with indomethacin, NS-398 or H89 enhanced LPS-induced cytokine production and neutrophil extracellular trap generation. Exposure to physiological concentrations of PGE2 suppressed the anti-microbial activity of monocytes, neutrophils and MDMs of HC, but did not influence efferocytosis. In a formyl-peptide receptor-1 dependent manner, mtDAMP treatment significantly increased COX-2 protein expression in neutrophils and monocytes, which resulted in increased PGE2 production. Conclusions: Physiological concentrations of PGE2 suppress the anti-microbial activities of neutrophils, monocytes and MDMs. Targeting the PGE2 pathway could be a therapeutic approach by which to enhance innate immune function post-injury.